A Cross-sectional Study on Measurement of Experienced Burnout among Health Care Professionals in Saudi Hospitals in Riyadh, Saudi Arabia - Asmaa Alyaemni (Issues and Development in Health Research Vol. 6, 2021)
Objectives: To measure the prevalence and causes of burnout among Health Care Professionals (HCPs) in four hospitals in Saudi Arabia. Background: Burnout is a mental illness caused by the failure of coping techniques that people often employ to deal with work stress, as a result of prolonged exposure to psychological factors. Burnout has the potential to be costly to employees, patients, and healthcare systems. Burnout has been linked to indices of personal suffering since the 1980s, including physical tiredness, insomnia, an increase in marriage and family problems, and even an increase in the use of alcohol and other drugs. Methodology: We used the Maslach Burnout Inventory-Human Services Survey (MBI-HSS). It assesses the four components of burnout; Emotional Execution (EE), Depersonalization (DP), low Personal Accomplishment (PA) and involvement. The total score was calculated by method 1 in Maslach Burnout inventory, 4th edition for medicine subgroup. Results: The main findings of this study show that doctors and nurses have the highest risk of experiencing burnout and that burnout more prevalent among those who work in emergency care and inpatient wards. Saudi and married physicians scored higher burnout while young and inexperienced nurses were more inclined to report emotional execution and low involvement in the work. Also, the study showed that physicians and men were not able to practice adaptive stress-coping strategies. Conclusion: the study emphasized the importance of work environment factors and suggested that the lack of involvement in work is an alarming predictor of burnout in public hospitals. Hospitals management should consider reducing demanding tasks and increasing rewards with a coaching leadership style, including instructional and emotional support.